The Impact of Physiological and Nutritional Factors on Anorexia Pediatric Patients: A Cross-Sectional Study at Al-Najaf Al-Ashraf - Obaid, Sarah Abbas; Saleem, Saad; Mohammed, Hassanein Fadel (Medical Science Journal for Advance Research, 2026)
Background: An eating disorder is a mental disorder defined by abnormal eating behaviors that adversely affect a person’s physical or mental health. These behaviors may include eating either too much or too little. Materials and Methods: This search included Harvesting the Convenience sampling about (195; 93 males, 102 femals) of anorexia cases noticed in the children where collected these data from records of Al-Najaf Al Ashraf health department/ Primary health center (Al-Qadisiyah District Center), Descriptive statistically, case control, Qi square at the level of probability of the significant differences (P<0.05) applying the statistical program SAS version 2010 by using Qi square. Results: The results showed cases of eating disorders in with different factors (Gender, Ages, Birth method, Feeding method, and vitamins intake), and according to gender of executed cases found in females compared with males. Regarding with ages these results appeared superiority in anorexia numbers at [(7-12) months;(1-3)yrs.] Compared with another especially in more than 6 years that had 3 cases only with of eating disorders. In other hand there were highest cases of established children patients with normal birth method in comparison with opposition situations found in caesarean section. In Children who ate Breast feeding enrolled, high numbers of anorexia in contrast to children patients with artificial feeding. Finally the children that had not vitamins appeared high numbers and percentage in comparison with another of cases. The results found decreased in weigh of males more than female. Anorexia cases found in different ages of patients from less than 1 months to more than 6 years with no significant differences. Concerning with birth methods. The babies born naturally suffered from eating disorders compared to others who were born by caesarean section with significant effectiveness. Also most cases of eating disorders were found in breastfed children, and the least affected was in the method of artificial feeding. The results of his study showed significant effectiveness about income factors with anorexia cases in pediatric patients, especially the superiority in families with insufficient income rates and percentage in comparison with another(partially and sufficient. The significant effectiveness of vitamins intake in these patients had anorexia via the highest rates and percentages found in children didn’t intake any vitamins compared with another in which had not have any eating disorders situations. Conclusions: There are cases of eating disorders in pediatric patients, The existence of a significant effect of (gender, vitamins intake, income, birth and feeding methods) in the manifestation of cases of malnutrition in pediatric patients, There is no significant effect of ages difference in showing cases of anorexia in pediatric patients.